Stabilization of Hypoxia-Inducible Factor Promotes Antimicrobial Activity of Human Macrophages Against Mycobacterium tuberculosis - Zenk, Sebastian F.; Hauck, Sebastian; Mayer, Daniel; Grieshober, Mark; Stenger, Steffen (Frontiers in Immunology, 2021)
Hypoxia-inducible factor (HIF) is a key oxygen sensor that controls gene expression patterns to adapt cellular metabolism to hypoxia. Pharmacological inhibition of prolyl-hydroxylases stabilizes HIFs and mimics hypoxia, leading to increased expression of more than 300 genes. Whether the genetic program initialized by HIFs affects immune responses against microbial pathogens, is not well studied. Recently we showed that hypoxia enhances antimicrobial activity against Mycobacterium tuberculosis (Mtb) in human macrophages. The objective of this study was to evaluate whether the oxygen sensor HIF is involved in hypoxia-mediated antimycobacterial activity. Treatment of Mtb-infected macrophages with the prolyl-hydroxylase inhibitor Molidustat reduced the release of TNFα and IL-10, two key cytokines involved in the immune response in tuberculosis. The reduction of cytokine release was associated with an interference of Molidustat with the p38 MAP kinase pathway. HIF-stabilization by Molidustat also induced the upregulation of the Vitamin D receptor and human β defensin 2, which define an antimicrobial effector pathway in human macrophages. Consequently, these immunological effects resulted in reduced proliferation of virulent Mtb in human macrophages. Therefore, HIFs may be attractive new candidates for host-directed therapies against infectious diseases caused by intracellular bacteria, including tuberculosis.